Differential effect of clopidogrel and ticagrelor on leukocyte count in relation to patient characteristics, biomarkers and genotype: a PLATO substudy. (3rd April 2022) - Nelson, Thomas A.; Parker, William A.E.; Ghukasyan Lakic, Tatevik; Westerbergh, Johan; James, Stefan K.; Siegbahn, Agneta; Becker, Richard C.; Himmelmann, Anders; Wallentin, Lars; Storey, Robert F.
Abstract: Inflammation plays a key role in cardiovascular disease by contributing to atherothrombosis. The PLATelet inhibition and patient Outcomes (PLATO) study (NCT00391872) compared ticagrelor to clopidogrel in patients with acute coronary syndromes and demonstrated fewer cardiovascular events with ticagrelor but lower white blood cell counts (WBC) with clopidogrel. In this further analysis of the PLATO biomarker substudy, we assessed associations between WBC and clinical characteristics, biomarker levels, and CYP2C19 polymorphisms. On-treatment mean (SD) WBC in the clopidogrel group was mildly reduced at each stage of follow-up compared with either the ticagrelor group (1 month: 7.27 (2.1) and 7.67 (2.23) x10 9 /L for clopidogrel and ticagrelor, respectively; p < .001) or following cessation of clopidogrel (7.23 (1.97) x10 9 /L, at 6 months vs 7.56 (2.28) x10 9 /L after treatment cessation; P < .001). This occurred independently of baseline biomarkers and CYP2C19 genotype (where known). Adjusting for clinical characteristics and other biomarkers, no significant interaction was detected between clinical risk factors and the observed effect of clopidogrel on WBC. Clopidogrel weakly suppresses WBC, independent of clinical characteristics, baseline inflammatory biomarker levels, and CYP2C19 genotype. Further work is required to determine the mechanism for this effect and whether it contributes to clopidogrel's efficacy as well as therapeutic interaction with anti-inflammatory drugs.